+0  
 
-6
245
1
avatar+956 

 Solve each equation and express your answer in simplest radical form:

 

5x - 7x2 = 3x + 4

 Apr 5, 2019
 #1
avatar+111392 
+1

5x - 7x^2 = 3x + 4    rearrange as

 

7x^2   - 2x +  4   =    0

 

Using the quadratic formula  with a = 7, b = -2  and c = 4     we have that

 

x  =  - (-2) ±  √[ (-2)^2 - 4*7 *4]             2 ±  √[ 4 - 112]            2 ±  √[-108]

        ______________________  =   ______________ =   ____________   =

                   2 (7)                                          14                             14

 

2 ± i √[ 9 * 3 * 4 ]             2 ±  6i√3             1 ± 3i √3

______________  =     _________  =     _________

           14                            14                         7

 

 

cool cool cool

 Apr 5, 2019

17 Online Users

avatar
avatar
avatar
avatar
avatar